Fanatisme dan Kontrol Diri dengan Agresi Verbal Penggemar Kpop di Media Sosial - Aswidi Nurpratami; Nurfitriany Fakhri; Andi Nasrawaty Hamid (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
The aim of this study to know the effect of Neuroticism to phubbing behavior on student of Makassar State University. This study used quantitative method as an approached and accidental sampling as a sampling technique. The respondent that involved in this study are 150 college students (n=150, 40 men and 110 women). This study used two instruments, they are neuroticism scale and phubbing scale that arrange as Likert scale. Neuroticism scale developed by researcher based on neuroticism aspect by McCrae dan Costa, that are anxiety, angry hostility, depression, self-consciousness, impulsiveness, and vulnerability. Phubbing scale that used in this study is an adaptation scale from Zulfikar, this scale developed based on two aspect from Karadağ, that are disturbance and phone obsession. The data of this study was analyzed use Ordinal Regression test with significance value 0,000 (p<0,05) and Nagelkerke value is 0,261. It means Neuroticism can affect phubbing behavior on college students of Makassar State University and the contribute of the effect is 26,1%. People with high neuroticism will cause excessive use of cell phones in order to reduce negative feelings, this excessive use of cell phones implicated to phubbing behavior appear and increase.